Cassava (Manihot esculenta Crantz) a tropical root crop - Álvarez Luna, E. (International Center for Tropical Agriculture, 1972)
Brief data are given on the origin and geographic distribution of cassava, uses and nutritional value. The importance of research efforts is pointed out. (CIAT)